In-vitro models of biocompatibility testing for restorative dental materials: From 2D cultures to organs on-a-chip. (15th September 2022) - Franca, Cristiane Miranda; Balbinot, Gabriela de Souza; Cunha, Diana; Saboia, Vicente de Paulo Aragão; Ferracane, Jack; Bertassoni, Luiz E.
Abstract: Dental caries is a biofilm-mediated, diet-modulated, multifactorial and dynamic disease that affects more than 90% of adults in Western countries. The current treatment for decayed tissue is based on using materials to replace the lost enamel or dentin. More than 500 million dental restorations are placed annually worldwide, and materials used for these purposes either directly or indirectly interact with dentin and pulp tissues. The development and understanding of the effects of restorative dental materials are based on different in-vitro and in-vivo tests, which have been evolving with time. In this review, we first discuss the characteristics of the tooth and the dentin-pulp interface that are unique for materials testing. Subsequently, we discuss frequently used in-vitro tests to evaluate the biocompatibility of dental materials commonly used for restorative procedures. Finally, we present our perspective on the future directions for biological research on dental materials using tissue engineering and organs on-a-chip approaches. Statement of significance: Dental caries is still the most prevalent infectious disease globally, requiring more than 500 million restorations to be placed every year. Regrettably, the failure rates of such restorations are still high. Those rates are partially based on the fact that current platforms to test dental materials are somewhat inaccurate in reproducing critical components of the complex oral microenvironment. Thus, there is a collective effort to develop new materials while evolving the platforms to test them. In this context, the present review critically discusses in-vitro models used to evaluate the biocompatibility of restorative dental materials and brings a perspective on future directions for tissue-engineered and organs-on-a-chip platforms for testing new dental materials. Graphical abstract: Image, graphical abstract